EUPATORIUM AYAPANA LEAF EXTRACTS ENHANCE ANTIOXIDANT POTENTIAL IN EHRLICH’S ASCITES CARCINOMA - BEARING SWISS ALBINO MICE : Pharmaceutical Science-Phytochemistry - BEPARI, MADHUBANTI; MAITY, PRALAY; SINHA, BANADEB; CHOUDHURY, SUJATA MAITI (International Journal of Life Science and Pharma Research, 2013)
Medicinal plants have gained significant importance in the potential management of cancer. Eupatorium ayapana, belonging to the Asteraceae, is therapeutically used as an antiseptic, antidysenteric, antibacterial and haemostatic agent. The present study was aimed to evaluate the antioxidant potential of ethanolic (EEEAL) and water extracts (WEEAL) of Eupatorium ayapana leaf in Ehrlich’s ascites carcinoma-bearing Swiss albino mice. EEEAL, WEEAL were administered intraperitoneally at the dose level of 150 mg/kg b ody weight/day for consecutive 14 days after 24 hours of EAC cell inoculation (1×106 cell) to mice using 5- fluorouracil as standard drug. Treatment with the extracts decreased the levels of hepatic and renal malon-dialdehyde (MDA), oxidized glutathione (GSSG) and increased reduced glutathione (GSH) level, catalase (CAT) and super oxide dismutase (SOD) activity in EAC-bearing mice. The study reveals that the extracts of Eupatorium ayapana leaf exhibit antioxidant activities in Ehrlich’s ascites carcinoma-bearing Swiss albino mice.